Effects of D3 supplementation on ovulation in polycyctic ovarian syndrome (PCOS) patients - Al-Mosawi, Reyadh H.; Hamood, Nuha J. (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: To explore the relation between vitamin D3 and ovulation in PCOS patients with vitamin D3 deficiency. Patients and Methods: 66 Patients were recruited from a private clinic in Karbala city / Al-Hindiya district. Criteria for selecting patients: aged 20-37 years, history of infertility, PCOS with low D3 blood level (<10ng/ml). The patients were divided into two groups (33 patients each), the first group treated with metformin 850mg, b.i.d, and placebo. The second group treated with metformin 850mg, b.i.d and vitamin D3 oral supplementation 5000 IU/day for 3 months. Ultrasonography was performed monthly on day 13 to assess the follicular size. D3 blood level was measured at the end of the 3 months. Data underwent one-way ANOVA testing and Dunnett’s test for multiple comparisons. Conclusion: The important finding was that D3 might affect follicular maturation in PCOS patients.